108 Effect of Revalor-XH, Revalor-200, and combination Revalor-IH/Revalor-200 on Yearling Heifer Growth Performance and Carcass Characteristics. (30th November 2020) - Carlson, Zachary; Coulson, Caitlin; Erickson, Galen E; Jordon, D J; Cooper, Rob; Scott, Tony; Bundy, Sheri; Nuttelman, Brandon
Abstract: A commercial feedlot trial utilizing 1, 728 crossbred heifers (initial BW = 410; SD = 10 kg) examined three implant strategies on growth performance and carcass characteristics. Treatments included: 1) Revalor-200 (REV-200) on d 1; 2) Revalor-IH on d 1 and Revalor-200 on d 56 (REV-IH/200; range 54-58 d) to target approximately 80 d with terminal implant; and 3) Revalor-XH (REV-XH) on d 1. Heifers implanted with REV-IH/200 combination had greater carcass-adjusted final BW and G:F compared to REV-200 and REV-XH (637 vs. 630 and 630 kg; 0.146 vs. 0.140 and 0.140, respectively; P ≤ 0.05). There were no differences (P ≥ 0.24) observed for live performance including final BW, DMI, or ADG on a live basis among implant strategies. Hot carcass weights and LM area improved for REV-IH/200 implanted heifers relative to REV-200 and REV-XH implanted heifers (397 vs. 393 and 393 kg; 90.9 vs. 87.7 and 88.7 cm 2, respectively; P ≤ 0.05). Dressing percent was greater for REV-IH/200 implanted heifers compared to REV-200 and REV-XH (62.7 vs. 62.1 and 62.2 %, respectively; P = 0.01). Marbling score and 12 th -rib fat thickness were not different (P ≥ 0.12) among implant treatments. Calculated yield grades improved for REV-IH/200 compared to REV-200 (3.63 vs. 3.82, respectively; P = 0.05). Heifers implanted with REV-IH/200 had a significant (P < 0.01) shift to a lower calculated yield grade distribution compared to REV-200 and REV-XH implanted heifers. The REV-IH/200 combination provided 280 mg of trenbolone acetate (TBA) and 28 mg estradiol (E2), while total active ingredient doses for REV-200 and REV-XH are 200 mg TBA and 20 mg E2. Thus, the greater concentration of TBA and E2 provided by REV-IH/200 combination improved carcass adjusted growth and carcass performance compared to the non-coated REV-200 implant and partially coated REV-XH implant.